Preparation, support and training requirements of South African expatriates - A. J. Vögel; J. J. Van Vuuren; S. M. Millard (South African Journal of Business Management, 2008)
A major Issue in international human resource management is the failure of expatriates. The failure rate of expatriates has been reported to range anywhere between 10 and 80 percent, costing multinational enterprises (MNEs) between US40 000 and US1 million for each failed assignment. In order to address the problem it is recommended that MNEs provide sufficient preparation, support and training to not only the expatriate but also to their trailing spouses and children. This research has, however, proven that not only are South African MNEs not providing the preparation, support and training required by their expatriates, they are also falling short in the preparation, support and training provided to expatriate's trailing spouses and children. The research does, however, provide guidelines on the preparation, support and training that can be offered to expatriates, their trailing spouses and children.
Keywords: 650